2010
DOI: 10.1007/s12011-009-8605-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Elements and Relationships Among Elements in Human Hippocampus, Dentate Gyrus, and Fornix

Abstract: To elucidate compositional changes of the limbic system with aging, the authors investigated age-related changes of elements in the hippocampus, dentate gyrus, and fornix and the relationships among elements by direct chemical analysis. After ordinary dissections at Nara Medical University were finished, the hippocampi, dentate gyri, and fornices were resected from identical cerebra of the subjects which consisted of 23 men and 23 women, ranging in age from 70 to 101 years. After ashing with nitric acid and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…These results suggest that, even within a clearly labeled tract such as the anterior fornix, its diffusivity changes can be highly heterogeneous. Our results are consistent with other literature which reports decreased FA values in the fornix with age [37,38]. While studies have shown that age-independent demyelination or axonal injury strongly correlates with specific DTI metrics such as RD or AD, respectively [39,40,41], it is unsurprising to see changes in FA, AD and RD in our current study sample given that multiple events involving different aspects of white matter integrity are involved in aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that, even within a clearly labeled tract such as the anterior fornix, its diffusivity changes can be highly heterogeneous. Our results are consistent with other literature which reports decreased FA values in the fornix with age [37,38]. While studies have shown that age-independent demyelination or axonal injury strongly correlates with specific DTI metrics such as RD or AD, respectively [39,40,41], it is unsurprising to see changes in FA, AD and RD in our current study sample given that multiple events involving different aspects of white matter integrity are involved in aging.…”
Section: Discussionsupporting
confidence: 93%
“…While it is known that the volume of the hippocampus decreases with age [38,44,45], we did not observe a significant decline in hippocampal volume in our group of healthy subjects. Longitudinal studies have demonstrated that there is whole-brain, and especially hippocampal, atrophy with age which correlates with a decline in cognition [46].…”
Section: Discussioncontrasting
confidence: 88%
“…In serum, it has been documented for Cu by Ghayour-Mobarhan et al (2005) and Kouremenou-Dona et al (2006); for Se by Lopes et al (2004). In brain, Markesbery et al (1984), Ongkana et al (2010) and Tohno et al (2010)  data converted from nmol/L Table 6. Manganese in Controls and Patients (µg/L) elements.…”
Section: Agementioning
confidence: 99%
“…Therefore, myelin has a selectively high P concentration with low levels of other elements [17,18]. Recently, the authors examined the P content in both the white and gray matters of the brain and confirmed that the P content was higher in the white matter than in the gray matter [3]. Riehemann et al [19] investigated the concentrations of different phosphorus compounds in the frontal lobe of 32 healthy subjects by image selected in vivo spectroscopy sequence on a whole-body scanner and reported that healthy females exhibited increased values of inorganic phosphate and decreased values of phosphocreatine in comparison to their male counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…To elucidate compositional changes of the brain with aging, the authors previously investigated age-related changes of elements in the corpus callosum [1], anterior commissure [2], and fornix [3] of the white matter and the pineal body [4], olfactory bulb and tract [5], mammillary body [6], hippocampus, and dentate gyrus [3] of the gray matter and found that the Ca content increased significantly in the mammillary body and hippocampus with aging, and the Mg content increased significantly in the hippocampus and fornix with aging.…”
Section: Introductionmentioning
confidence: 99%